Image and video compression : fundamentals, techniques, and applications - Joshi, Madhuri A., author 382620; Raval, Mehul S. , author; Dandawate, Yogesh H. , author; Joshi,Kalyani R. J, author; Metkar, Shilpa P. M , author (Boca Raton, FL : CRC Press, Taylor & Francis Group)
"Preface This book is intended primarily for courses in image compression techniques for undergraduate through postgraduate students, research scholars, and engineers working in the field. It presents the basic concepts and technologies in a student-friendly manner. The major techniques in image compression are explained with informative illustrations, and the concepts are evolved from the basics. Practical implementation is demonstrated with MATLAB